HUBUNGAN MINAT TERHADAP HASIL BELAJAR SISWA DALAM PEMBELAJARAN SENI TARI DI SMP N 4 PADANG - Suci Audina Rahmi; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2018)
AbstractThis article aims to identify and describe the correlation of interest with the study results of dance learning in SMP N 4 Padang.The type of research used was quantitative research with correlation method (relationship). The correlational research was intended to examine the presence or absence of the correlation of students’ interest towards learning outcomes of dance art of 8th-grade students of SMP N 4 Padang. Population in this research was all 8th-grade students of SMP N 4 Padang or 220 students, while the sample of research was 69 students of 8th-grade students of SMPN 4 Padang who were randomly selected. Instruments used to obtain the data were questionnaire research and student learning outcomes in the Odd semester (1) academic year 2017/2018. The results showed that there was a significant relationship between students' interest towards the learning outcome. It is proved by the value of rcalculatedwas 0,628 and rtable.was 0,237 at a significant level of 5%, so that it can be concluded that rcalculatedwas bigger than rtable. Hence, Ho hypothesis was rejected and Ha was accepted. It means that there is a significant correlation between interest and students’ study result of dance learning.Keywords: correlation, interest, dance art